2011
DOI: 10.1590/s0066-782x2011001400018
|View full text |Cite
|
Sign up to set email alerts
|

Biofilme em marca-passo artificial: ficção ou realidade?

Abstract: Cardiac pacing through cardiac pacemaker is one of the most promising alternatives in the treatment of arrhythmias, but it can cause reactions natural or complex reactions, either early or late. This study aimed to describe the scientific evidence on the risk of infection and biofilm formation associated with cardiac pacemaker. This is a study of integrative literature review. It included 14 publications classified into three thematic categories: diagnosis (microbiological and/or clinical), complications and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 20 publications
(92 reference statements)
0
19
0
2
Order By: Relevance
“…However, though there are some reports of treatment only with antibiotics, which have been curative, most patients suffer an infective exacerbation with bacteremia, and severe complications necessitating surgical removal of the entire pacing system for cure, as in the second episode of case 1 [2, 3, 8]. This may be the result of biofilm production complicating eradication by antibiotics [9]. In a study investigating marginal and subgingival plaque formation Cardiobacterium species were shown to be part of the plaques in smokers [10]; in case 1 chronic apical parodontitis was actually diagnosed and three teeth removed.…”
Section: Discussionmentioning
confidence: 99%
“…However, though there are some reports of treatment only with antibiotics, which have been curative, most patients suffer an infective exacerbation with bacteremia, and severe complications necessitating surgical removal of the entire pacing system for cure, as in the second episode of case 1 [2, 3, 8]. This may be the result of biofilm production complicating eradication by antibiotics [9]. In a study investigating marginal and subgingival plaque formation Cardiobacterium species were shown to be part of the plaques in smokers [10]; in case 1 chronic apical parodontitis was actually diagnosed and three teeth removed.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on whether there is an implanted device involved in the biofilm formation, biofilm infections are divided into two major groups: device-related and tissue-related. Numerous medical devices have been found to be associated with the occurrence of biofilm infections, including orthopedic alloplastic devices [ 14 , 15 ], indwelling urinary catheters or urethral stents [ 16 , 17 ], intravenous catheters [ 18 ], vascular prostheses [ 19 ], cardiac pacemakers and prosthetic heart valves [ 4 , 16 , 20 ], endotracheal tubes [ 21 ], cerebrospinal fluid shunts [ 22 ], peritoneal dialysis catheters [ 23 ], biliary tract stents [ 24 ], intrauterine devices [ 25 , 26 ], contact lenses [ 27 ], tissue fillers [ 28 , 29 ], and dentures [ 30 ]. Biofilm infections that are not associated with implanted devices include the chronic airway infection commonly seen in patients with cystic fibrosis [ 31 ], chronic obstructive pulmonary diseases [ 32 ], tuberculosis [ 33 ], chronic wound infections [ 34 ], chronic otitis media [ 35 ], and chronic sinusitis [ 36 ].…”
Section: Biofilm Formation and Related Infectionsmentioning
confidence: 99%
“…However, as a consequent, bacterial biofilm infections become also frequent. It has been reported that vast majority, if not all, of the medical devices or prostheses may result in biofilm infections, which include intravenous catheters, 9 vascular prosthesis, 10 cerebrospinal fluid shunts, 11 prosthetic heart valves, 12 urinary catheters, 12 joint prostheses and orthopedic fixation devices, 13 cardiac pacemakers, 14 peritoneal dialysis catheters, 15 intrauterine devices, 16 biliary tract stents, 17 dentures, 18 breast implants, 19 contact lenses 20 and in the dental area caries and periodontitis, and so on. In addition, there are also biofilm infections not associated with foreign bodies, such as chronic airway infections in cystic fibrosis (CF) patients 21 or patients with chronic obstructive pulmonary diseases, 22 native valve endocarditis, chronic otitis media, 23 chronic sinusitis 24 and chronic (diabetes) wound infections.…”
Section: Introductionmentioning
confidence: 99%